Kids vs aliens - Eisener, Jason; Davies, John, 1982-; Mariche, Dominic; Rex, Phoebe; MacDonald, Calem; Percival, Asher Grayson; RLJE Films (Firm); Shudder Films (United States RLJE Films, 2023)
All Gary wants is to make awesome home movies with his best buds. All his older sister Samantha wants is to hang with the cool kids. When their parents head out of town on one Halloween weekend, an all-time rager of a teen house party turns to terror when aliens attack, forcing the siblings to band together to survive the night.
Title from container.
Originally released as a motion picture in 2022.
Wide screen.
Dominic Mariche, Phoebe Rex, Calem MacDonald, Asher Grayson Percival.
Rating: Not rated.
DVD; widescreen (1.78:1); Dolby 5.1.
Keywords: Human-alien encounters -- Drama; Extraterrestrial beings -- Drama; Teenagers -- Drama; Halloween -- Drama; Siblings -- Drama; Parties -- Drama; Drama; Feature films; Fiction films; Horror films; Science fiction films; Video recordings for the hearing impaired